Evaluation of thiazide diuretic use as preferred therapy in uncomplicated essential hypertension patients - Greene, Ronald S. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Thiazide diuretics are effective antihypertensive medications shown to reduce the risk of cardiovascular events and stroke. Despite being the preferred choice for uncomplicated essential hypertension, thiazide diuretics continue to be underutilized. METHODS: Uncomplicated essential hypertension patients taking a single antihypertensive medication were evaluated upon enrollment, diagnosis after enrollment or initiation of therapy in treatment naïve patients. Clinician prescribing habits were determined for both pre-existing and newly diagnosed hypertensive patients. For the cost savings analysis, hydrochlorothiazide (HCTZ) 25mg daily was selected as the preferred conversion medication. RESULTS: Four hundred seventy-eight patients were included. ACE inhibitors were the most prescribed at 35.4% (n=169), followed by dihydropyridine calcium channel blockers (DHP CCB) and thiazide diuretics, both at 20.3% (n=97). Only 12.9% (n=33) of patients with hypertension that were taking an antihypertensive medication upon enrollment were either continued or started on thiazide diuretic therapy. Newly diagnosed or treatment naïve patients were prescribed a thiazide diuretic 28.8% (n=64) of the time. DHP CCB accounted for 58.8% of the total medication cost per month with thiazide diuretics responsible for 0.8% of the cost. If all patients had been prescribed HCTZ 25mg daily, 95.8% of the total medication cost per month could have been saved. CONCLUSIONS: Thiazide diuretics were underutilized as preferred therapy in patients with pre-existing or newly diagnosed uncomplicated essential hypertension. While cost of therapy should not be the sole reason for medication selection, thiazide diuretics are an attractive option and should be considered as a preferred therapy in this patient population.